Perceptions of the Catalan educational Inspectorate on its situation and needs, as of the approval of the Decree of autonomy of centers (2010) - Segura Torres, Joan; Gairín Sallán, Joaquín; Silva, Patricia (Avances en Supervisión Educativa, 2018)
The purpose of the study is knowing the opinion about the Educational Inspection functioning after the approval of the Catalan Education Law (2009) and the subsequent Autonomy Decrees (2010) and School managements (2010) to identify their needs. Taking the opinion of 88 inspectors, 12 interviews and 2 discussion groups, it is concluded that the Inspection must evolve towards a more practical and face-to-face reality and less bureaucratic, defining and selecting its tasks and functions.